Effect of Organizational Structure, Leadership and Trust on Job Performance of Employee:A Case Study on Employee at Universitas Ternama - Setiawan, Bambang Moertono; Putrawan, I. Made; Murni, Syliviana; Ghozali, Imam (International Review of Management and Marketing, 2016)
The objective of the research is to obtain the direct effect of organizational structure, leadership and trust on the performance of employee of Ternama University. The study was conducted at Ternama Universityin 2010 by using a survey method with path analysis applied in testing hypothesis and 80 samples selected by simple random sampling. The finding of the research are: (1) there is a direct effect of organizational structure on trust; (2) there is a direct effect of organizational structureon performance; (3) there is a direct effect of leadership on trust; (4) there is a direct effect of leadershipon performance; (5) there is a direct effect of truston performance; (6) there is a indirect effect of organizational structure on performance through trust, and (7) there is a indirect effect of leadershipon performance through trust.Based on these findings, it could be concluded that any changing or variation occured at performance might have been directly significant effected by trustand leadership, and also indirectly significant effected by organizational structure and leadership.Therefore, when we want to minimize the variation which occurred in performance, these factors such as trust,leadershipand organizational structure are necessary to be taken into account. Keywords: Organizational Structure, Leadership, Trust and Performance JEL Classifications: L2, L22, L25